Terms of endearment eaudiobook - McMurtry, Larry (Terms of Endearment, 2013)
A widow with a small army of suitors, Aurora Greenway loves the limelight. She's got three grandchildren whom she adores (in small doses) and her son-in-law Flap, whom she's not really crazy about. And there's her daughter Emma. In some ways, Emma is all there ever was. Now, there's little time left to say the things that need to be said.